Effect of Evaporation Boat-Substrate Distance on the Formation of Zinc Oxide Nanostructures - Iman Ahmad; Yasir Mohammed; Khaldoon N. Abbas (College of Education for Pure Sciences, 2022)
Zinc Oxide (ZnO) is one of the important semiconductor materials which contribute effectively to the development of the semiconductor industry technology. ZnO nanostructures (NSs) were synthesized using thermal chemical vapor deposition (TCVD) technique under atmospheric pressure at different evaporation boat-substrate distances. ZnO NSs were prepared by oxidizing Znic acetate dihydrate powder within quartz tube instead of its outside. The effect of change evaporation boat-substrate distance (2.5, 4.5, 6.5 and 8.5 cm) on the optical and structural properties of ZnO NSs were studied. ZnO NSs were characterized by UV-Visible spectrophotometer, X-ray diffraction (XRD) technique and photoluminescence (PL) spectroscopy to evaluate its optical and structural properties. Optical band gap measurement results exhibited a red-shifted from (3.25 eV) to (3.05 eV), as the separation distance increased from (2.5 cm) to (8.5 cm), respectively. XRD technique confirms that metal oxide was ZnO and having hexagonal structure. The average crystallite size of the samples was decreased from 63.4 to 58.3 nm, with the increase in separation distance from 2.5 to 8.5 cm. Also, the sharpness, strong intensity and narrow width of dominant diffraction peak indicate the high crystallinity of the prepared ZnO NSs. The PL spectra of the ZnO NSs revealed a wide deep-level emission for all the prepared samples. ZnO NSs grown by TCVD technique may provide potential applications in nano-photovoltaics and nano-photodetectors.